Cytotoxicity study of benzo[a]pyrene on blood cells of Wistar rat in vitro - Zhang, J.; Liu, Y.; Wei, S-Z. (Cellular and Molecular Biology, 2016)
The effect of benzo[a]pyrene (BaP) on Wistar rat lymphocyte activity, lymphocyle membrane integrity and erythrocytes hemolysis were examined using the MTT assay, the release of the lactate dehydrogenase (LD) and the hemoglobin release respectively in vitro. The results showed that lymphocyte activity had no remarkable response to BaP after a low dose of exposure. But the membrane change was found after higher dose of BaP exposure, and the significant release of LD was observed. The release of LD increased with exposure time prolonging and exposure dose increasing. The results also showed that BaP didn’t change the release of hemoglobin from erythrocytes. But the release of hemoglobin was affected significantly by synergistic effects of BaP and pentachlorophenol (PCP) and the release of hemoglobin increased with the dose of the mixture of BaP and PCP. Therefore, there is an obvious cytotoxicity of BaP in lower dose to blood cells of Wistar rat. The damage of lymphocyte membrane is more sensitive than lymphocyte activity and erythrocytes hemolysis to lower dose of BaP. It is suggested that the release of LD as a biomarker could be used to monitor and evaluate the contamination of BaP. The blood of Wistar rats were taken and checked after a fixed time interval (6 hours) of acute BaP exposure. The level of whole genomic DNA methylation was found to decrease significantly in the blood of rats.